2023
DOI: 10.1002/adfm.202300878
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Small Molecule Donor with Terminal Branching Position Directly Attached to the Backbone Enables Efficient All‐Small‐Molecule Organic Solar Cells with Excellent Stability

Abstract: All‐small‐molecule organic solar cells (ASM‐OSCs) are challenging for their inadequate efficiency and device stability due to their more susceptive morphology. Herein, a family of isomeric small molecule donors (SMDs) is synthesized based on the benzodithiophene–terthiophene core with linear, 1st carbon, and 2nd carbon position branched butyl‐based rhodanine for ASM‐OSCs, respectively. The single crystal of thiophene‐substituted model T‐s‐Bu forms a more compact intermolecular packing with herringbone structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Recently, Wang and co-authors have synthesized three isomeric SMDs with linear (SM- n -Bu), 1st carbon (SM- s -Bu), and 2nd carbon-position (SM- i -Bu) branched isomeric terminal alkyl chain-based rhodanine end groups. 51 The neat films of SMDs with branched terminal chains exhibited slightly blue-shifted absorption spectra, up-shifted LUMO levels, and down-shifted HOMO levels. The blend film based on SM- s -Bu:BO-4Cl showed the optimal blend morphology characterized by nanofiber-based phase separation with pronounced BO-4Cl microcrystals, resulting in the highest and balanced charge mobility and the weakest charge recombination.…”
Section: Improve the Stability Of Oscs Through Materials Designmentioning
confidence: 95%
“…Recently, Wang and co-authors have synthesized three isomeric SMDs with linear (SM- n -Bu), 1st carbon (SM- s -Bu), and 2nd carbon-position (SM- i -Bu) branched isomeric terminal alkyl chain-based rhodanine end groups. 51 The neat films of SMDs with branched terminal chains exhibited slightly blue-shifted absorption spectra, up-shifted LUMO levels, and down-shifted HOMO levels. The blend film based on SM- s -Bu:BO-4Cl showed the optimal blend morphology characterized by nanofiber-based phase separation with pronounced BO-4Cl microcrystals, resulting in the highest and balanced charge mobility and the weakest charge recombination.…”
Section: Improve the Stability Of Oscs Through Materials Designmentioning
confidence: 95%
“…Bulk-heterojunction (BHJ) organic solar cells (OSCs) have been regarded as a promising energy conversion technology due to their unique characteristics of lightweight, flexibility, and solution processability. In recent years, the advent of narrow band-gap small-molecule acceptors (SMAs), particularly Y6 and its derivatives, has significantly improved the power conversion efficiencies (PCEs) of OSCs based on polymer donors and small-molecule acceptors, surpassing 19%. Unlike polymer photovoltaic materials, small-molecule photovoltaic materials offer advantages such as precisely defined chemical structure, minimal batch-to-batch variations, and easy purification. As a result, there has been a remarkable focus on all-small-molecule organic solar cells (ASM-OSCs), which have shown substantial advancements. Specifically, the PCEs of binary ASM-OSCs have exceeded 17%, while ternary ASM-OSCs have surpassed 18%. , …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] With recent innovation of device-processing engineering and photovoltaic materials, particularly the development of Y-series acceptors, the power conversion efficiencies (PCEs) of the ASM-OSCs have surpassed 16%. [26][27][28][29][30] However, the PCEs of the ASM-OSCs still lag behind those of the polymer-based OSCs. 31,32 Therefore, engineering high-performance small molecule donors (SMDs) is crucial for enhancing the PCEs of the ASM-OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In A-D-A type SMDs with benzo[1,2-b:4,5-b 0 ]dithiophene (BDT) as the donor unit, the terminal group plays a crucial role in controlling the absorption, energy level and aggregation propensity, among other factors. 28,33,34 For instance, Ge's group reported a suite of SMDs using 1H-indene-1,3(2H)-dione, 2-ethylhexyl rhodanine and cyanoacetic acid esters as terminal groups, respectively. They found that varying the end-group can affect the packing morphology of the active layer, leading to different p-p interactions and distinct photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%